A method of constructing programmed motions of a mechanical system - Sanh, Do (Vietnam Journal of Mechanics, 1998)
In the paper the method for constructing programmed motion is represented. The requirements for the programmed motion are treated as ideal constraints in analytical mechanics. The programmed motions expressed in Lagrange coordinates and in quasi coordinates are investigated. By applying the form of equations of motion of a constrained mechanical system [7], a schema for calculating programmed motions has been established. By this schema the errors of realizing programmed motions have been reduced and controlled. For illustration of the method some examples have been investigated.